2015
DOI: 10.1111/ijsa.12119
|View full text |Cite
|
Sign up to set email alerts
|

Self‐promotion Statements in Video Resumes: Frequency, intensity, and gender effects on job applicant evaluation

Abstract: Although video resumes have received a substantial amount of media attention and there seems to be a growing awareness among Human Resource professionals of video‐based job applications, little is known about the effect of video resumes on applicant evaluation. This research investigates the effectiveness of self‐promotion within the context of video resumes. Self‐promotion frequency and intensity and applicant gender were manipulated. Ratings by recruiters and college students indicate that high levels of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
1
13
0
1
Order By: Relevance
“…Fourth , inspection of the correlation table (see Table 1 ) indicated that correlations were not overly strong and in line with what could be expected (e.g., no relation between job suitability ratings of any of the applicant profiles on the one hand and social desirable responding, educational level, and job level on the other hand). Finally, as literature suggests that recruiters’ gender and recruiting experience might affect resume evaluations (e.g., Cole et al, 2003 , 2007 ; Waung et al, 2015 ), we also checked whether participants’ gender and recruiting experience needed to be controlled for in the main analyses ( Bernerth and Aguinis, 2016 ). Gender and resume screening experience related significantly to the job suitability ratings of some of the applicant profiles/resumes.…”
Section: Resultsmentioning
confidence: 99%
“…Fourth , inspection of the correlation table (see Table 1 ) indicated that correlations were not overly strong and in line with what could be expected (e.g., no relation between job suitability ratings of any of the applicant profiles on the one hand and social desirable responding, educational level, and job level on the other hand). Finally, as literature suggests that recruiters’ gender and recruiting experience might affect resume evaluations (e.g., Cole et al, 2003 , 2007 ; Waung et al, 2015 ), we also checked whether participants’ gender and recruiting experience needed to be controlled for in the main analyses ( Bernerth and Aguinis, 2016 ). Gender and resume screening experience related significantly to the job suitability ratings of some of the applicant profiles/resumes.…”
Section: Resultsmentioning
confidence: 99%
“…Third, inspection of the correlation table (see Table 1 ) indicated that correlations were not overly strong, except for ‘years’ and ‘self-rated proficiency’ of interview experience ( r = 0.85) which may pose a threat to collinearity and therefore were not included into the same model. Further, as research has already shown that recruiter and applicant gender might interact with job applicant evaluations due to stereotypes (e.g., Bolino and Turnley, 2003 ; Tyler and McCullough, 2009 ; Smith et al, 2013 ; Waung et al, 2015 ), and because one’s age might affect how lenient/strict one evaluates others ( Wright et al, 2016 ), we also checked whether raters’ gender and age needed to be controlled for in the main analyses ( Berneth and Aguinis, 2016 ). Participants’ gender and age, however, were not included as they did not appear to be good covariates (i.e., gender and age did not relate to the dependent variable).…”
Section: Resultsmentioning
confidence: 99%
“…However, laboratory research using an undergraduate sample suggested that evaluations of applied social skills and mental capabilities of applicants were lower when those evaluations were based solely on video resumes as opposed to when those evaluations were based solely on paper resumes (Waung, Hymes, & Beatty, 2014). In addition, a follow-up study utilizing a recruiter and student sample demonstrated the ineffectiveness of high levels of self-promotion in video resumes for men and the possible detrimental effects of high levels of self-promotion in video resumes for women (Waung, Hymes, Beatty, & McAuslan, 2015). From an applicant perspective, caution needs to be exercised when it comes to the use of video-based resumes as the aforementioned research suggests that they are also likely to be a less effective format than traditional resumes.…”
Section: Overall Resume Formatmentioning
confidence: 99%
“…This is especially the case when the impression management tactic used is of high intensity (e.g., "While working on this project I was told that I was an ideal [emphasis added] example to the newer interns due to my positive attitude and unfailing [emphasis added] professionalism"; Waung et al, 2015, p. 349) as high levels of self-promotion in video resumes were ineffective and this negative impact was strongest for male applicants (Waung et al, 2015).…”
Section: Impression Managementmentioning
confidence: 99%